Achieving Flow: An Exploratory Investigation of Elite College Athletes and Musicians - Antonini Philippe, Roberta; Singer, Sarah Morgana; Jaeger, Joshua E. E.; Biasutti, Michele; Sinnett, Scott (Frontiers in Psychology, 2022)
While studies on the characteristics of flow states and their relation to peak performance exist, little is known about the dynamics by which flow states emerge and develop over time. The current paper qualitatively explores the necessary pre-conditions to enter flow, and the development of flow over time until its termination. Using an elicitation interview, participants (10 athletes and 12 musicians) were asked to recall their flow experiences in sports or music performances. The analysis resulted in the identification of following three phases that athletes and musicians experience during flow: (1) Preparation to enter flow; (2) Entry into the flow state and; (3) Exit from the flow state. These three phases are characterized by several sub-themes contributing to the experience of flow. The function of emotions is crucial, as they play a core role across all three phases and regulate flow over time. The findings provide insights into the phenomenological characteristics of the transition and maintenance of the three proposed phases and the temporal dynamics of flow.